WATER USE IN OLIVE ORCHARDS ESTIMATED BY PHYSIOLOGIC AND CLIMATIC METHODS IN TUNISIA - Amani, Bchir; Olfa, Boussadia; Raoul, Lemeur; Mohamed, Braham (European Scientific Journal, ESJ, 2013)
This experimental study conducted on irrigated olive trees (cv. Meski) in arid climate in Enfidha-Tunisia. This study aims to estimate the water needs of the Olive Trees for a possible optimization of irrigation. To do this, a calculation of water requirements was performed by physiologic and climatic methods and compared to traditional irrigation practiced by farmer (T0). The physiologic method is based on the xylem sap flow (T1) and the climatic method is based on the reference evapotranspiration (T2). Results showed that the values of the highest transpiration are recorded under 60% ET0 (T2).Under this treatment, the average of transpiration was about 50% of the applied irrigation dose, with soil evaporation average about 15%. These results allowed us to conclude that the physiological method (T1) allows a better estimate of water needs. This method also improves the profitability of the olive tree with a better optimization of water use (save 35% of water).